If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11(2x-1)=8(2x-1)+35
We move all terms to the left:
11(2x-1)-(8(2x-1)+35)=0
We multiply parentheses
22x-(8(2x-1)+35)-11=0
We calculate terms in parentheses: -(8(2x-1)+35), so:We get rid of parentheses
8(2x-1)+35
We multiply parentheses
16x-8+35
We add all the numbers together, and all the variables
16x+27
Back to the equation:
-(16x+27)
22x-16x-27-11=0
We add all the numbers together, and all the variables
6x-38=0
We move all terms containing x to the left, all other terms to the right
6x=38
x=38/6
x=6+1/3
| 6x–64=2x+44 | | 6u-1=9u-13 | | 2w-97=w-25 | | 0.60x+0.05(20-x)=0.10(-78) | | 3(b−2)+5=7+3(2−5)−38 | | 5w-37=w+7 | | V+6v=28 | | 7p=5p+4 | | 4x+1.5=3(x−1)+2 | | 6w-99=5w-77=5w-82 | | -5=2m-14 | | 4p-65=15 | | (x+2)/10=12 | | 34+90/n=44 | | |4r|+8=32 | | -8=4(v-4)-6v | | 2x-13=5x+15 | | 9+20d=89 | | 97=13d-98 | | 27x+19=21 | | 97=5b-93 | | 4*p+2=3*10 | | 3+12p=99 | | 65=f/5+48 | | 19=60/a+9 | | 2x-15=4x+18 | | 2+7k=23 | | 5x-27=x-12 | | 100=5x-100 | | 63=58+90/h | | 5x-27=2x+3 | | 4=v/13 |